Characterization of ClpS2, an essential adaptor protein for the cyanobacterium Synechococcus elongatus. Issue 24 (24th November 2015) - Tryggvesson, Anders; Ståhlberg, Frida M.; Töpel, Mats; Tanabe, Noriaki; Mogk, Axel; Clarke, Adrian K.
Abstract : The adaptor protein ClpS associates to the Clp protease and promotes degradation of N‐end rule substrates in eubacteria and in algal/plant chloroplasts. Cyanobacteria are unusual in having two distinct ClpS paralogs. Although ClpSl is typical of bacterial ClpS, ClpS2 differs in crucial ways. ClpS2 in Synechococcus elongatus is a relatively low‐abundant, soluble protein essential for phototrophic growth. Like ClpSl, ClpS2 binds to the ClpCP3/R protease to block α‐casein degradation and promote that of N‐end rule substrates in vitro . However, their substrate specificity differs, with ClpSl recognizing destabilizing Phe and Tyr residues at the substrate N‐terminus whereas ClpS2 recognizes Leu. Overall, ClpS2 appears to have independently evolved in cyanobacteria to degrade a particular group of proteins, whose turnover is vital for cell viability. Abstract : Cyanobacteria possess two distinct paralogs of the adaptor protein CIpS. ClpS1 has characteristics typical of bacterial CIpS proteins whereas ClpS2 differs. The relatively low‐abundant ClpS2 is essential for phototrophic growth. ClpS1 and ClpS2 bind to the ClpCP3/R protease and alter its substrate specificity. The two CIpS proteins target different types of N‐end rule substrates.